SANKSI PIDANA UNDANG-UNDANG KEHUTANAN BAGAIKAN PALU PEMBUNUH SEMUT - Amrullah Arpan (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2020)
The law is guidance for human being, the last task of the law is to protect every one as regards fundamental rights (including right for life). For rural community, his life still depends on woods to make their houses and so on. The other side they have not free to take the product of forest and woods. With out license of government, it is the crime act, and to get the license they must pay contribution. That contribution is expensive and need long time until finish. Is it fair to punish them as criminals.